LEXICOGRAPHY TYPES OF DICTIONARIES (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
Lexicography as a field represents the combined art, science, and technique of dictionary-making, analysis, and research. Dictionaries, the most visible products of lexicography, manifest in a stunning variety of types and serve vastly different purposes, reflecting not only the complexities of language but also its users and their multifaceted needs. The various types of dictionaries highlight both the evolution of lexicographical theory and practice, as well as the linguistic, cultural, and technological complexities that intertwine with the compilation, description, and transmission of vocabulary.